2010
DOI: 10.1142/s0217732310032366
|View full text |Cite
|
Sign up to set email alerts
|

Phantom Mimicry on the Normal Branch of a DGP-Inspired Braneworld Scenario With Curvature Effect

Abstract: It has been shown recently that phantom-like effect can be realized on the normal branch of the DGP setup without introduction of any phantom matter neither in the bulk nor on the brane and therefore without violation of the null energy condition. It has been shown also that inclusion of the Gauss-Bonnet term in the bulk action modifies this picture via curvature effects. Here, based on the Lue-Starkman conjecture on the dynamical screening of the brane cosmological constant in the DGP setup, we extend this pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 117 publications
(244 reference statements)
0
4
0
Order By: Relevance
“…It has been shown that modifying the geometric part of the Einstein field equations alone leads to an effective phantom like behavior while there is no phantom field in the problem ( see Ref. [44][45][46][47]) . Now we show that modified teleparallel gravity (f (T ) gravity) can realize an effective phantom-like behavior while the null energy condition for the effective cosmic (torsion) fluid, that is, (ρ (T ) + P (T ) ≥ 0) is respected.…”
Section: Phantom-like Behavior In F (T ) Gravitymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that modifying the geometric part of the Einstein field equations alone leads to an effective phantom like behavior while there is no phantom field in the problem ( see Ref. [44][45][46][47]) . Now we show that modified teleparallel gravity (f (T ) gravity) can realize an effective phantom-like behavior while the null energy condition for the effective cosmic (torsion) fluid, that is, (ρ (T ) + P (T ) ≥ 0) is respected.…”
Section: Phantom-like Behavior In F (T ) Gravitymentioning
confidence: 99%
“…Typically for realization of such a behavior phantom fields are considered, while the existence of phantom field causes instabilities and violates the null energy condition [41][42][43]. Possible realization of phantom-like behavior in some cosmologi-cal models such as the DGP braneworld model [44][45][46] and f (R) gravity are studied [47]. Also possible existence of a phantom-like phase in teleparallel and also modified teleparalel gravity theories has been studied in some references such as Refs.…”
Section: Introductionmentioning
confidence: 99%
“…(1.2) has solutions k(G) = c 1 G + c 2 G (1−p)/4 with constants c 1 and c 2 -compare with eqs. (59) and (60) of [16]. The term c 1 G is a divergence, and so does not contribute to the field equation, so, seemingly, only power-law Lagrangians k(G) = G (1−p)/4 produce the exact solution a(t) = t p .…”
Section: Introductionmentioning
confidence: 99%
“…In [44], the following strict result is shown: Exact power-law cosmic expansion in f (R) gravity models with perfect fluid as source is possible for f (R) = R n only. Newer models of this kind can be found in [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], and [81].…”
Section: Introductionmentioning
confidence: 99%